2022
DOI: 10.1101/2022.02.02.478800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of cell size on morphogen gradient precision

Abstract: Patterning during embryonic development is remarkably precise and reproducible. How high patterning precision is achieved is still largely elusive. Here, we use a novel simulation framework to determine the impact of cell size on the variability of morphogen gradients and the positional information they convey. We find that both variability in the cell diameter and spatial averaging of the local concentration affect the sensed gradient variability only little. In contrast, the mean cell diameter has a profound… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(36 citation statements)
references
References 84 publications
3
33
0
Order By: Relevance
“…We previously showed that in case of linear decay, there is a negligible impact of cell area variability as long as CVA < 1 [19]. We now find that this holds similarly for non-linear decay (Fig.…”
Section: Impact Of Non-linear Decay On Gradient Precisionsupporting
confidence: 80%
See 4 more Smart Citations
“…We previously showed that in case of linear decay, there is a negligible impact of cell area variability as long as CVA < 1 [19]. We now find that this holds similarly for non-linear decay (Fig.…”
Section: Impact Of Non-linear Decay On Gradient Precisionsupporting
confidence: 80%
“…No-flux boundary conditions were used at both outer ends of the domain: We generated large numbers of variable morphogen gradients by numerically solving Eq. 9 with kinetic parameters p, d and D , and cell areas A independently drawn from log-normal distributions for each cell in the domain, as described before [2, 19]. The diffusion coefficient, D , and the degradation rate, d , set the steady-state patterning length scale, , and we report positional quantities relative to the average λ or the average cell diameter, which in turn is chosen to be a fixed multiple of the average λ .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations